2011
DOI: 10.1002/term.395
|View full text |Cite
|
Sign up to set email alerts
|

The small molecule PKA-specific cyclic AMP analogue as an inducer of osteoblast-like cells differentiation and mineralization

Abstract: Osteoblastic differentiation is an important landmark for bone formation, bone repair and regeneration, however it is a very complex process controlled by different signaling mechanisms. Several groups have reported that the cyclic adenosine monophosphate (cAMP) signaling system is responsible for regulating osteoblast cell differentiation. Nonetheless, to date, the principle role of the cAMP molecules related to this process remains controversial. Moreover, the underlying cAMP-dependent signaling cascade gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 48 publications
1
43
0
Order By: Relevance
“…For instance, a small molecule could be identified to activate signaling pathways that stimulate osteoblast-associated gene expression and matrix mineralization, which are processes associated with bone formation [199]. In fact, data from our group and others demonstrated that small molecule cyclic adenosine monophosphate (cAMP) analogs were able to induce in vitro and in vivo bone formation through the Protein Kinase A (PKA)/cAMP response element-binding protein (CREB) signaling mechanism [200][201][202][203]. It is also worth noting that the advances in high throughput screening technologies have yielded a large number of other osteoinductive small molecules in the past decade [176].…”
Section: Small Molecule Deliverymentioning
confidence: 94%
“…For instance, a small molecule could be identified to activate signaling pathways that stimulate osteoblast-associated gene expression and matrix mineralization, which are processes associated with bone formation [199]. In fact, data from our group and others demonstrated that small molecule cyclic adenosine monophosphate (cAMP) analogs were able to induce in vitro and in vivo bone formation through the Protein Kinase A (PKA)/cAMP response element-binding protein (CREB) signaling mechanism [200][201][202][203]. It is also worth noting that the advances in high throughput screening technologies have yielded a large number of other osteoinductive small molecules in the past decade [176].…”
Section: Small Molecule Deliverymentioning
confidence: 94%
“…Via a similar mechanism, utilizing a small molecule phenamil, our group recently reported in vitro bone formation through the downregulation of Smurf1 in sintered PLGA microsphere scaffolds [232]. In addition to BMP/smad pathway, several other pathways such as protein kinase A (PKA) simulated by 4-Bnz-cAMP,Wnt, Hh, and BMP/MAPK signaling cascades have also been observed to induce osteogenesis [233236]. Other small molecules that have been observed to induce bone formation by these pathways include rapamycin, FK-506, and tilorone [237].…”
Section: Bone Regenerationmentioning
confidence: 99%
“…Growth factors stimulate cell expansion and maintain cell-stemness, whereas stimulated cAMP signalling stops cells dividing and stimulates spontaneous cell differentiation. The cAMP/PKA pathway acts as a regulator of neurite outgrowth/regeneration and osteoblast cell differentiation in several experimental systems (Tegenge et al 2011;Lo et al 2011). The differences in the responses of the cell lines to the db-cAMP stimuli here suggest that isolated adult progenitor cells possess diverse differentiation potential.…”
Section: Discussionmentioning
confidence: 86%